2002
DOI: 10.1021/jf020761g
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of a Direct ELISA and an HPLC Method for Glyphosate Determinations in Water

Abstract: A competitive direct enzyme-linked immunosorbent assay (ELISA) and high-pressure liquid chromatographic (HPLC) methods were compared in terms of accuracy and precision for the detection and quantification of glyphosate-spiked Nanopure, tap, and river waters. The ELISA had a detection limit of 0.6 ng mL(-)(1) and a linear working range of 1-25 ng mL(-)(1), whereas the HPLC method had a detection limit of 50 ng mL(-)(1) and a linear working range of 100-10000 ng mL(-)(l). No statistically significant differences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
49
0
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(54 citation statements)
references
References 26 publications
3
49
0
2
Order By: Relevance
“…The limit of detection and quantification were 0.17 and 0.53 μg mL -1 , respectively. The LOD is consistent with the maximum contaminant level for drinking water in the United States of 0.7 μg mL -1 , 40 and also the concentration of 0.28 μg mL -1 recommended by Health and Welfare Canada in the Canadian Water Quality Guidelines. 40 …”
Section: Analytical Curve Lod and Loqsupporting
confidence: 83%
“…The limit of detection and quantification were 0.17 and 0.53 μg mL -1 , respectively. The LOD is consistent with the maximum contaminant level for drinking water in the United States of 0.7 μg mL -1 , 40 and also the concentration of 0.28 μg mL -1 recommended by Health and Welfare Canada in the Canadian Water Quality Guidelines. 40 …”
Section: Analytical Curve Lod and Loqsupporting
confidence: 83%
“…This lack of data may be linked to the high polarity of the molecule, close in structure to many naturally occurring amino acids, that makes its detection difficult in water samples (Skark et al, 1998;Rubio et al, 2003). This difficulty is probably worsened by the low concentrations occurring in coastal waters.…”
Section: Pesticide Exposurementioning
confidence: 99%
“…It has been shown that both HPLC and ELISA are comparable in terms of accuracy and precision for detection and quantification of glyphosate in water-based analysis and including Nanopure, tap and river waters. Water-based solvents for glyphosate demonstrate a detection limit of 0.6 ng/mL and a linear functional range of 1-25 ng/mL [200]. However, HPLC was not able to achieve detection below 5 ppb; 1 hence, in cases including water-based vaccines, analysis using numerous sample runs was made including using two independent labs to test the same samples.…”
Section: Glyphosate Contamination In Collagen Enzymes Gelatin and Vmentioning
confidence: 99%